The levels of depression, anxiety and stress on pre and post knee arthroplasty patients - Abdul Razak, Ardilla Hanim; Zulkifly, Ahmad Hafiz; Musa, Ramli; Awang, Mohd Shukrimi; Goh, Kian Liang (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
The purpose of this study is to measure the outcome of total knee arthroplasty pre and post operative using validated questionnaires; Depression, Anxiety, Stress Scale (DASS21). The study was done prospectively in which questionnaires were distributed pre and post operatively. This study concentrated more on patients’ perception rather than surgeons’ perception. This study focus on both aspects of patients’ expectation as it covers physical and emotional outcome measures.